CEO compensation in early‐stage firms: Rewards for prospectivity and survival. (19th December 2020) - Bui, Thi; Ferguson, Andrew; Lam, Peter
Abstract: Prior studies on chief executive officer (CEO) compensation focus mainly on large firms. This paper aims to suggest new factors associated with CEO compensation for small, homogeneous firms, specifically, Australian early‐stage mining exploration entities (MEEs). We document a set of predictors of CEO compensation proxying for economic performance, including geological prospectivity components of the exploration and evaluation (E&E) asset account and proceeds from equity raisings that enhances survival probabilities. We find positive associations between these predictors and CEO remuneration. In terms of CEO pay mix, we find that E&E asset acquisitions and equity proceeds are both positively associated with the proportion of option value in CEO total compensation. This suggests MEEs allocate their cash resources to investment opportunities, rather than CEO compensation. Overall, these findings, coupled with a significant and positive pay‐performance relation, provide evidence supporting efficient compensation practices in the MEE context.